The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/nnano.2015.243
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular crowding creates heterogeneous environments of gene expression in picolitre droplets

Abstract: Understanding the dynamics of complex enzymatic reactions in highly crowded small volumes is crucial for the development of synthetic minimal cells. Compartmentalised biochemical reactions in cell-sized containers exhibit a degree of randomness due to the small number of molecules involved. However, it is unknown how the physical environment contributes to the stochastic nature of multistep enzymatic processes. Here, we present a robust method to quantify gene expression noise in vitro using droplet microfluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 41 publications
3
118
0
Order By: Relevance
“…They found that the DNA copy number and macromolecular crowding were the key factors to the heterogeneous gene expression, which directly increased the system's stochasticity. [82] Moreover, they also used an agarose droplet system to analyze the cellular heterogeneity of cytokine secretion in cancer cells. This system encapsulates cells together with functionalized cytokine-capture beads for subsequent binding, and for following detection of secreted cytokines at single-cell level.…”
Section: High Throughputmentioning
confidence: 99%
“…They found that the DNA copy number and macromolecular crowding were the key factors to the heterogeneous gene expression, which directly increased the system's stochasticity. [82] Moreover, they also used an agarose droplet system to analyze the cellular heterogeneity of cytokine secretion in cancer cells. This system encapsulates cells together with functionalized cytokine-capture beads for subsequent binding, and for following detection of secreted cytokines at single-cell level.…”
Section: High Throughputmentioning
confidence: 99%
“…Numerous theoretical and experimental studies have suggested both the need for and the challenge to correcting simulation methods to account for the effects of crowding on assembly processes (e.g., [129, 166]). Examples include the effects on several aspects of DNA replication such as helicase activity and the sensitivity of DNA polymerase to salt [1], on protein-protein binding affinity and specificity [99], on the kinetics and morphology of amyloid self-assembly [115], on the stochasticity of gene expression machinery [76], and on viral capsid assembly [175, 36]. …”
Section: Self-assembly Modeling and Simulationmentioning
confidence: 99%
“…154 Indeed, crowding effects within picoliter droplets containing DNA and polymerases in vitro enhances the retention of transcriptional machinery and enhanced RNA synthesis at transcription sites. 155 This may be an important contributing factor to the early stages of CB nucleation by enhancing snRNA gene transcription.…”
Section: Proteinmentioning
confidence: 99%